VISUAL ANALYSIS OF CIRENDEU BATIK MOTIFS - Damayanti, Anandhita Alvina; Falah, Asep Miftahul (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
This research is based on the emergence of Cimahi Batik asan identity of the city in the context of its 8th anniversary,which took place on June 21, 2009. The culture and naturalresources of the town of Cimahi inspofCimahi batik. Oneof the motifs that characterize Cimahi batik is the Cirendeumotif. The inhabitants of the traditional village of Cirendeuare known to consume cassava and Sunda Wiwitan beliefs.So far, the development of Cirendeu batik motifs has beeninspired only by culture and natural sources of inspiration,especially as inspiration for batik motifs and colors. Theresearch uses qualitative methods because the object ofthe study is to understand and interpret the meaning ofCirendeu batik motifs, which aim to develop the conceptof sensitivity to discuss the problems encountered, explainthe reality related to the pursuit of theory from below, andcreate an understanding of the phenomena experienced.This study also uses Edmund Burke Feldman’s theoreticalapproach to art criticism. In this theory, four phases areknown in the analysis of the work: description, formalanalysis, interpretation, and evaluation. The results ofthis research are the reappraisal and development of oneof the identities of Cimahi, namely batik, the reappraisaland development of Cireundeu batik motifs, whichhave outstanding natural and cultural potential, and theuncovering of the symbolic meanings of color signs andsymbols, which are the characteristics of Cimahi batik.Keywords: Motifs, Cimahi, Batik Cirendeu.